Engineered extracellular matrix components do not alter the immunomodulatory properties of mesenchymal stromal cells in vitro - Wehner, Rebekka; Taubert, Christina; Mende, Tanja; Gaebler, Christian; Andrade, Ana Valéria Gouveia de; Bornhäuser, Martin; Werner, Carsten; Tonn, Torsten; Schäkel, Knut; Bachmann, Michael; Schmitz, Marc (Journal of tissue engineering and regenerative medicine, 2013)
Mesenchymal stromal cells (MSCs) have emerged as promising candidates for regenerative therapies, including tissue engineering. Recently it has been reported that engineered extracellular matrix (ECM) components support the differentiation of MSCs into osteocytes and chondrocytes, indicating that ECM components may represent attractive carriers for MSC transplants to repair damaged tissues. However, little is known about the impact of engineered ECM components on the immunosuppressive properties of MSCs, which may essentially contribute to the prevention of allogeneic MSC transplant rejection. In the present study, we explored the potential of fibronectin, fibrillar collagen I, tropocollagen and collagen I/heparin to influence the immunosuppressive capacities of MSCs. We found that these ECM components do not modulate the capability of MSCs to inhibit the proliferation of anti-CD3/anti-CD28 antibody-stimulated CD4+ and CD8+ T cells and of lymphocytes in a mixed lymphocyte reaction. In addition, the potential of MSCs to impair the production of immunostimulatory IL-12 and to improve the release of immunosuppressive IL-10 by 6-sulpho LacNAc+ (slan) dendritic cells (DCs), representing a pro-inflammatory subset of human blood DCs, was not altered by the ECM components. Furthermore, ECM components do not influence the ability of MSCs to inhibit the slanDC-induced proliferation of CD4+ T cells. In conclusion, the used engineered ECMs maintain important immunosuppressive properties of MSCs, which support their suitablility as carriers for MSC transplants in tissue engineering.
Published online 18 May 2012
Gesehen am 18.10.2021